IMPLEMENTATION OF ANDROID-BASED SYSTEM THROUGH HAVERSINE METHODS FOR BABY CARE SERVICES - Nisar Nisar; Wasilah Wasilah; Septilia Arfida; Tia Almani (Prosiding International conference on Information Technology and Business (ICITB), 2020)
The baby care businesses were developing rapidly together with the rapid-growing technology and the lifestyle of people recently. There were several baby care businesses with various facilities in Bandar Lampung, e.g., spa, haircut, make up, hair dye, and others. The problem statement of this study was that 1) the customers had to come to the baby care location to buy the products so that it caused a long queue and made inconvenience for customers because the Covid-19 outbreak were still happening; 2) there was also no information regarding the closest way to reach the baby care location so that it confused the customers. The objective of this study was determining the closest way through the Haversine formula. The Haversine formula was used to determine the location through the geo-location technology (API from Google Map) based on the latitude and longitude coordinates of its location. The system development method used in this study was through the prototype model used to fulfill the users’ needs for the system. The result of this study was that the system was able to provide information on the closest way from the user location to baby care locations and to display the types of provided services, prices, and order service for the babies. This system was expected to support the effective and efficient business processes.KEYWORDS: Haversine, Baby Care Services, Prototype, Android-Based System.